2015
DOI: 10.1093/ijnp/pyv073
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine Administration Attenuates Methamphetamine-Induced Novel Object Recognition Deficits

Abstract: Background:Previous studies have demonstrated that methamphetamine abuse leads to memory deficits and these are associated with relapse. Furthermore, extensive evidence indicates that nicotine prevents and/or improves memory deficits in different models of cognitive dysfunction and these nicotinic effects might be mediated by hippocampal or cortical nicotinic acetylcholine receptors. The present study investigated whether nicotine attenuates methamphetamine-induced novel object recognition deficits in rats and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 74 publications
(127 reference statements)
1
9
0
Order By: Relevance
“…To examine hippocampus-independent object memory, the mice were subjected to a novel object recognition test after 19–20 weeks of running. This test was conducted in an open field arena (30 cm × 30 cm) as described previously [42]. Both training and trial session duration was 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…To examine hippocampus-independent object memory, the mice were subjected to a novel object recognition test after 19–20 weeks of running. This test was conducted in an open field arena (30 cm × 30 cm) as described previously [42]. Both training and trial session duration was 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…Eight slices (four per rat) were mounted on each Superfrost Plus glass microslide (VWR International, Radnor, PA) and stored at 280°C for subsequent use in autoradiography assays. Hippocampal and perirhinal cortex tissues were also analyzed and data were reported in a separate article (Vieira-Brock et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Results from preclinical studies also suggest that nicotine may alleviate some of the adverse consequences of chronic stimulant use. A recent series of studies found that nicotine exposure attenuated METH-induced disruptions in cognitive performance and striatal deficits possibly through activation of α4β2 receptors [122124]. Nicotine and other nAChR agonists have also been shown to ameliorate disruptions in cognitive performance in monkeys with a history of cocaine self-administration [125].…”
Section: Nicotine + Stimulant Interactionsmentioning
confidence: 99%